COVID-19 Vaccines—All You Want to Know - Shishido, Akira A.; Barnes, Ashley H.; Narayanan, Shivakumar; Chua, Joel V. (Seminars in Respiratory and Critical Care Medicine, 2023)
The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic has led to an unprecedented public health crisis. The collective global response has led to production of multiple safe and effective vaccines utilizing novel platforms to combat the virus that have propelled the field of vaccinology forward. Significant challenges to universal vaccine effectiveness remain, including immune evasion by SARS-CoV-2 variants, waning of immune response, inadequate knowledge of correlates of protection, and dosing in special populations. This review serves as a detailed evaluation of the development of the current SARS-CoV-2 vaccines, their effectiveness, and challenges to their deployment as a preventive tool.
Keywords: COVID-19; SARS-CoV-2; vaccines; variants; immunity